Uncertainty, populism and foreign direct investment: the state of play in economic research - Marijana Andrijić (Public Sector Economics)
This paper provides a synthesized, critical overview of the latest economic literature regarding the linkage between three concepts – uncertainty, populism and foreign direct investment. It starts with summarising ways to measure uncertainty in a direct and an indirect manner (with their respective advantages and limitations) and estimate its effects on populism and foreign direct investment. Later on, the paper focuses on the link between populism and foreign direct investment, exploring the possible role of uncertainty in this context. While heightened uncertainty and populism are typically associated with negative economic (including a decline in foreign direct investment) and non-economic outcomes, the nature of these effects and their interpretation are complex and leave room for further investigation. The implications of the research on this topic are wide reaching not only for economic stakeholders, but also for public sector policy practitioners.